On modelling coolant penetration into the microchannels at the tool-workpiece interface - Wei, Wenming; Robles-Linares, Jose A.; Liao, Zhirong; Wang, Zhao; Luna, Gonzalo Garcia; Billingham, John; Axinte, Dragos (Journal of Manufacturing Processes, 2022)
A network of microchannels is formed at the interface between the cutting tool and the workpiece during machining due to their rough surface structures. The penetration of coolant into these microchannels has a great effect on the machined surface quality by changing the frictional behaviour and heat transfer characteristics of the interfaces. Most of the present studies focus on the macroscopic coolant delivery process but the mechanism of the microscopic penetration phenomena in the channels at the interface remains unclear. Thus, this study proposes a multi-scale and multi-phase comprehensive theoretical model by combining the machining process, coolant flowing in microchannels and lubrication process, to analyse the coolant transportation in the microchannels and investigate its lubrication effects and the friction mechanisms at the interface between the tool and the workpiece. Then, an orthogonal turning testing of Inconel 718 is designed to verify the proposed model. The cooling and lubrication effect of coolant in the microchannels on the reduction of tool wear, contact length, cutting force and temperature has been demonstrated. And the improvement of chip fragment and microstructure has also been revealed.
Keywords: Industrial and Manufacturing Engineering; Management Science and Operations Research; Strategy and Management